THE EFFECT OF ADDING LIQUID SMOKE FLAVOR WITH DIFFERENT CONCENTRATIONS ON SENSORIC QUALITY OF CATFISH (Pangasius hypophthalmus) “OTAK-OTAK” - Rusdy Tarmizi; Tjipto Leksono; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Catfish is one of the leading commodities in the fisheries sector. Fias “otak-otak” is a gel product made from fish meat mixed with tapioca and spices such as salt, sugar, thick coconut milk, garlic, shallots, and pepper. The function of technology for making fish “otak-otak” is as an effort to diversify processed fish products in the form of a gel which is expected to have added value. Liquid smoke is a compound that evaporates simultaneously from a hot reactor through the pyrolysis technique (decomposition with heat) and condenses in the cooling system. Liquid smoke has the main components, namely acids, phenol derivatives, and carbonyls which act as flavoring and color-forming. The purpose of this study was to determine the effect of adding liquid smoke flavor with different concentrations on the sensory quality characteristics of the catfish brains produced. The experimental research method conducted experiments with different types of fish treatment on the quality of pempek, with a non-factorial Completely Randomized Design (CRD) with 4 levels, namely without the addition of 0% liquid smoke (P0), 0.5% liquid smoke addition (P1), and the addition of smoke. 1% liquid (P2), the addition of 1.5% liquid smoke (P3). Calculation of the amount of liquid smoke is calculated from the amount of fish meat. The treatment was repeated 3 times, so the experimental unit was 12 units. The results showed that the effect of adding liquid smoke flavor with different concentrations on the sensory quality of the catfish brains had a significant effect. The best treatment shown from the results of the sensory test was 0.5% (P1) which resulted in the quality of the fish brains being highly favored with a value of appearance of 8.2, aroma of 7.5, taste of 7.8, and texture of 7.8.Keywords: Fish Brains, Flavor, Organoleptic, Liquid Smoke.